Reality and Prospect of Electricity Production from Renewable Energies in Arab Countries: Analytical Study (1990–2017) - Rahmane, Amal; Bentafat, Abdelhak (International Journal of Energy Economics and Policy, 2018)
This study aims to highlight the status of electricity production from renewable energies in some Arab countries due to their potential; that could lead to an increase in the achievement of a significant part of sustainable development if it will be exploited. In addition,this study seeks to highlight the contribution of each renewable energy in producing electricity for every Arab country. One of the results of this study is that there is a very strong correlation (0.995) between electricity consumption and production in the considered countries, that means that the increase in electricity consumption is pushing the production to achieve self-sufficiency. Moreover,there is a weak and low correlation (-0.420) between the electricity production from renewables and CO2 emissions per capita, which means that the increase in the production of electricity from renewables in Arab countries reduces CO2 emissions per capita, and this is very logical. It should be noted that some Arab countries have taken rapid steps towards pioneering electricity production through renewables such as Egypt and Morocco. Keywords : electricity production, renewable energy, Arab region. JEL Classifications: O57, Q42, Q48 DOI: https://doi.org/10.32479/ijeep.6939